Investigation of wire-based laser directed energy deposition (DED) process for high-resolution submillimetre features - Wang, Xichen (Cranfield University, 2024)
In this thesis, the feasibility of manufacturing submillimetre-scale wall features using 250 W to 500 W and 1.00 kW to 2.79 kW laser power, from a 1.0 mm small beam to 1.5 mm – 3.0 mm large beams was investigated. The D-ratio correlates the beam diameter with wire diameter was introduced for deposition performance and wire position sensitivity discussion. The study firstly reveals the possibility of fabricating defect-free, smooth surface appearance and submillimetre-scale wall features using 500 W of laser power with large laser beam diameters of 1.50 mm to 2.00 mm (D-ratio of 2.50 to 3.33) without the plume interference. It was found that using a larger beam size can enhance the chance of deposition success due to enough specific point energy applied, a relatively lower but even distribution of the power density, and less energy discrepancy projected on wire and substrate, as a result, increase in the possibility of deposition success. This study also successfully applied 2.79 kW of high-level laser power and a large beam size of 3.00 mm (D-ratio of 5.00) to build the millimetre-scale wall features at a fast processing speed. It was found that fast processing speed, large laser beam size, and high-level laser power enable the chance of feeding more material into the melt pool, meanwhile, a larger D-ratio is needed for preventing the wire position sensitivity introduced back. A deposition rate of 400 g/h was achieved by using a 0.6 mm diameter wire and still exhibits the potential of fabricating submillimetre-scale wall features with the deposition rate potentially reaching 750 g/h, which is comparable to the conventional power-based laser DED process of 600 g/h. Finally, the possibility of applying FLMIPs in the wire-based laser directed energy deposition regime was revealed, but the comprehensive feasibility of applying these parameters in the wire-based laser directed energy deposition regime needs to be further investigated. These imply that wire-based laser DED process is capable of manufacturing submillimetre-scale features with good performance at relatively large beam sizes and has the potential to achieve competitively high deposition rates in submillimetre-scale features to satisfy the rapid manufacturing requirements in the additive manufacturing regime.
Rodrigues Pardal, Goncalo - Associate Supervisor
Keywords: Laser wire additive manufacturing; thin-wall structure; high resolution; 316L stainless steel; large laser beam size; interaction time; specific point energy; power density; surface energy density; WFS to TS ratio